Governing the galleys : jurisdiction, justice, and trade in the squadrons of the hispanic monarchy (sixteenth-seventeenth centuries) - Lomas Cortés, Manuel, (Themes in Biblical Narrative;, 2020)
The development of the Spanish Navy in the early modern Mediterranean triggered a change in the balance of political and economic power for the coastal populations of the Hispanic Monarchy. The establishment of new permanent squadrons, endowed with very broad jurisdictional powers, was the cause of many conflicts with the local authorities and had a direct influence on the economic and production activities of the region. Manuel Lomas analyzes the progressive consolidation of these institutions in the sixteenth and seventeenth centuries, their influence on the mechanisms of justice and commerce, and how they contributed to the reconfiguration of the jurisdictional system that governed the maritime trade in the Mediterranean.